Architektur. Landschaft/Architecture. Landscape Architekturjahrbuch Graz Steiermark 2013/Architecture Yearbook Graz Styria 2013 - Vries, Nathalie de 1965-; Guttmann, Eva 1967- (Ambra, 2014)
The Styrian Architecture Award has been awarded since 1980. This makes it an important indicator of buildings and their cultural importance in the state of Styria, which us known for its unique and richly varied architecture